509 Developing a Core Outcome Set for hospital deprescribing trials with older people under the care of a geriatrician. (13th April 2023) - Martin-Kerry, J; Taylor, J; Scott, S; Patel, M; Wright, D; Clark, A; Turner, D; Alldred, D P; Murphy, K; Keevil, V; Witham, M D; Kellar, I; et al.
Abstract: Introduction: Half of older people are prescribed unnecessary or harmful medication that are not routinely deprescribed in hospital. There is a need for trials of deprescribing interventions, and for these to adopt consistent measurement and reporting of outcomes(1). Aim: To develop a Core Outcome Set (COS) for use in hospital deprescribing trials for older people under the care of a geriatrician. Methods: We developed a list of potentially relevant outcomes from the literature. We sought representation from four stakeholder groups: older people and carers, hospital clinicians, hospital managers, and ageing/deprescribing researchers. A gatekeeper at 15 hospitals in England identified and provided study information to hospital staff by email; and older people taking ≥5 medicines, and their carers received printed study information. Academics were recruited worldwide. The number approached was not captured. Using a two-round Delphi survey of participants from all four stakeholder groups scored, each outcome according to Grading of Recommendations Assessment, Development and Evaluation (GRADE)(2). This was followed by two consensus workshops to finalise the COS by discussing the importance, feasibility and acceptability of outcomes. Results: In the Delphi survey, 200 people completed Round 1 and 114 completed Round 2. Representing all stakeholder groups, 10 people participated in Workshop 1 and 10 people in Workshop 2. Six outcomes were identified as most important, feasible and acceptable to collect in a trial and were included in the COS for hospital deprescribing trials with older people under the care of a geriatrician. These outcomes were: number of prescribed medicines stopped; number of prescribed medicines with dosage reduced; quality of life; mortality; adverse drug events and number of hospital stays. Three other outcomes were identified as important, but not currently feasible to collect: number of potentially inappropriate medicines prescribed; burden to the patient from their medication; and medication-related admissions to hospital. Conclusion: The COS provides the minimum outcomes that should be collected and reported in all hospital deprescribing trials for older people under the care of a geriatrician. This COS builds on three existing COS for: medication reviews in older people with polypharmacy; addressing polypharmacy in older people in primary care; and optimising prescribing in older people in nursing homes. However, it is important when developing a COS to involve all relevant stakeholders that will be affected by a COS, which in this case was older people under the care of a geriatrician and relevant hospital staff. The six outcomes in the COS were agreed as being the most important to be implemented in all hospital deprescribing trials for older people under the care of a geriatrician. The value of considering the feasibility of outcome data collection is demonstrated by the removal of three outcomes that may have compromised COS uptake. Adoption of the COS by hospital deprescribing trials for older people under the care of a geriatrician will enable results from trials to be compared and also allow future aggregation of trial data. References: 1. Lundby C, Pottegård A. Considerations regarding choice of primary outcome in clinical trials in deprescribing. British Journal of Clinical Pharmacology. 2022;88(7):3032–4. 2. Williamson PR, Altman DG, Blazeby JM, Clarke M, Devane D, Gargon E, et al. Developing core outcome sets for clinical trials: issues to consider. Trials. 2012;13(1):1–8.